2022
DOI: 10.1038/s41380-022-01866-3
|View full text |Cite
|
Sign up to set email alerts
|

Power and optimal study design in iPSC-based brain disease modelling

Abstract: Studies using induced pluripotent stem cells (iPSCs) are gaining momentum in brain disorder modelling, but optimal study designs are poorly defined. Here, we compare commonly used designs and statistical analysis for different research aims. Furthermore, we generated immunocytochemical, electrophysiological, and proteomic data from iPSC-derived neurons of five healthy subjects, analysed data variation and conducted power simulations. These analyses show that published case–control iPSC studies are generally un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
(57 reference statements)
1
15
0
Order By: Relevance
“…The iPSC lines from control individuals were obtained either commercially or from collaborators. Control line 1 was obtained from Coriell Institute for Medical Research (GM25256) and characterized using methods reported in ( 22 ) and ( 23 ). The donor was 30 years of age at the time of biopsy and is of Asian ancestry.…”
Section: Methodsmentioning
confidence: 99%
“…The iPSC lines from control individuals were obtained either commercially or from collaborators. Control line 1 was obtained from Coriell Institute for Medical Research (GM25256) and characterized using methods reported in ( 22 ) and ( 23 ). The donor was 30 years of age at the time of biopsy and is of Asian ancestry.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to classical rescue experiments in null mutant mouse neurons it offers the advantage of endogenous expression levels. This allows for direct assessment of the contribution of the mutation to the disease mechanism and offers higher statistical power compared to case–control designs in which patient-derived lines are compared to unrelated controls [ 49 ]. However, it does not test for potential interactions of the mutation with a patient’s genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…Recordings with series resistance of higher than 15 MΩ and leak current of more than 300 pA were excluded. Asynchronicity of single EPSCs was assessed by running the traces through an analysis pipeline described previously [ 49 ]. Recordings were deemed too asynchronous if the contribution of small additional peaks to the major peak was above the cutoff with user decision.…”
Section: Methodsmentioning
confidence: 99%
“…In animal studies, it is common to perform a power analysis based on effect size to prevent underpowered studies. It should become common practice to also perform these analyses for iPSC‐based studies to increase the applicability of the results (Brunner et al, 2022). Using this approach, we can fully utilize the potential of iPSC‐based studies to reveal mechanisms that apply to entire populations as well as those unique to individuals.…”
Section: Discussionmentioning
confidence: 99%